Understanding Premarital Sexual Behavior: A Qualitative Case Study among Male and Female College Students - Luthfiyah, Anis; Hayati, Elli Nur (Universitas Ahmad Dahlan, 2025)
Young individuals frequently engage in intimate relationships, specifically premarital sex, which is categorized as unsafe sexual behavior. Numerous studies have highlighted the premarital sexual behavior of females, who face greater risks compared to their male counterparts. Understanding how gender differences influence this behavior is crucial for developing targeted strategies to mitigate the potential negative consequences among young people. A qualitative case study was conducted to examine the premarital sexual behavior of students in Province X and to identify the factors influencing it. Six participants—three male and three female students—were selected through purposive snowball sampling. After providing consent for private interviews, qualitative in-depth discussions were carried out. The results from thematic analysis revealed eleven key themes related to their premarital sexual behavior and six themes associated with influencing factors. Males reported engaging in their first sexual intercourse at an earlier age during adolescence, while females tended to do so slightly later, in early adulthood. Notably, males expressed feelings of guilty pleasure regarding their premarital sexual activities, whereas females shared unpleasant experiences stemming from a lack of assertiveness in declining sexual advances from their partners. They also reported facing judgmental attitudes from healthcare workers during medical checkups. Similarities found included having multiple sexual partners, neglecting reproductive health, and feeling a disconnection from their religious beliefs. The implications of the study are discussed further.